ANALISIS DAN PERANCANGAN DECISION SUPPORT SYSTEM MENENTUKAN ANGKAT KREDIT DENGAN METODE SAW (SIMPLE ADDITIVE WEIGHTING) PADA LEASING OTO FINANCE - Muhamad Risdarianto Utomo; Tata Sutabri (CV. ADIBA AISHA AMIRA, 2023)
A leasing company is seeking a Credit Analyst to analyze the payment ability of credit applicants and conduct field surveys to reduce the risk of bad credit. To avoid errors in data analysis and calculations, a Credit Analyst must be very careful. Therefore, the company needs to use a computer-based system to assist in data analysis and assessment of credit applicant criteria. This system is designed using the Simple Additive Weighting (SAW) method, which is a Fuzzy Multiple Attribute Decision Making (FMADM) method. The SAW method is chosen because the criteria weighting is not too complicated. It is expected that this system will help the company reduce errors and speed up the credit applicant selection process.